Physics Teachers’ Perspectives on The Availability of The Integration of E-Formative Assessment in E-Learning based on Website (EFA in ELboW) during Covid-19 Pandemic - Romadhon, Utoro; Sukarmin, Sukarmin; Budiawanti, Sri (Journal of Education Reseach and Evaluation, 2021)
In the field of education, the COVID-19 demands changes in the learning process. It is important to know the changes that have occurred so that we can take some actions to face the changes that occurred, and help teachers prepare for the changes that occur in the learning process, especially in the physics learning process. This study aims to determine changes in the teaching, assessing, and using validated instrument aspect due to the COVID-19 pandemic. Also, gathered teacher perspectives on the availability of E-Formative Assessment in Web-based E-Learning (EFA on ElboW) integration. The sampling technique used in this study was quota sampling. Data were collected from 33 physics teachers from various districts in Indonesia and analyzed using quantitative descriptive. As a result, the significant value of paired sample test for teaching, assessing and using validated instrument aspect before and during COVID-19 successively are 0.000, 0.003, and 0.183. Then all respondents agreed that the Integration of E-Formative Assessment in Website-Based E-Learning (EFA in ELboW) was needed by physics teachers during the COVID-19 Pandemic. It can be concluded that there are changes in the teaching and assessing aspect. Also, the Integration of E-Formative Assessment in Website-Based E-Learning (EFA in ELboW) was needed by physics teachers to prepare them to deal with the changes that occur in learning due to the COVID-19 Pandemic. Of course, this article has great implication for teachers and researchers.